Onset of the Younger Dryas Recorded with 14C at Annual Resolution in French Subfossil Trees. Issue 4 (25th August 2020) - Capano, Manuela; Miramont, Cécile; Shindo, Lisa; Guibal, Frédéric; Marschal, Christian; Kromer, Bernd; Tuna, Thibaut; Bard, Edouard
ABSTRACT: Subfossil trees with their annual rings constitute the most accurate and precise archive to calibrate the radiocarbon ( 14 C) method. The Holocene part of the IntCal curve is based on tree-ring chronologies, absolutely dated by dendrochronological matching. For the Northern Hemisphere, the absolute curve starts at 12, 325 cal BP. For the early part of the Younger Dryas (YD) climatic event (≈ 12, 850–11, 650 cal BP), there are only a few floating dendrochronological sequences, mainly from Switzerland and France. We present new 14 C results from subfossil trees ( Pinus sylvestris L.) collected from the Barbiers site (southeast French Alps). The dendrochronological series covers 416 years, corresponding to the onset of the YD period. In order to date our sequence, we matched it with the 14 C record based on kauri trees from New Zealand. The Barbiers data were first averaged at the same decadal resolution as the kauri record. Statistical comparison of the different averaging options and matching techniques enables dating the Barbiers sequence to 13, 008–12, 594 ±10 cal BP, which thus includes the boundary between the Allerød and YD events. The new Barbiers record allows to calculate the 14 C inter-hemispheric gradient ( 14 C-IHG) during the period overlapping the kauri sequence. For the optimal dating option, the mean 14 C-IHG is 37 yr with a standard deviation (SD) of 21 yr based on 43 decadal estimations (−6‰ with SD of 2‰). The 14 C-IHG record exhibits minimal values, down to zero, between 12, 960–12, 840 cal BP. Excluding these minima leads to an average 14 C-IHG of 45 yr with a SD of 14 yr based on 33 decadal values, in agreement with observations for the last two millennia. The Barbiers record suggests a 14 C-IHG increase between the end of the Allerød period (IHG of 37 yr with SD of 14 yr) and the early part of the YD (IHG of 48 yr with SD of 14 yr), which is compatible with previously reported drop of deep-water convection in the North-Atlantic and the associated increase in wind-driven upwelling in the Southern Ocean.